Life cycle of Spodoptera frugiperda J. E. Smith FED with Pennisetum purpureum Schumach and Paspalum conjugatum PJ Bergius leaves - Putra Ichsan Luqmana Indra; Mahdiana Liana Fairuzzannah (BIO Web of Conferences)
Spodoptera frugiperda is a pest that entered Indonesia and attacks corn plants. This pest can use other plants to complete its life cycle. This study aims to analyze the growth and life cycle of S. frugiperda with three different food treatments. Parameters observed in this study were life cycle length, larval head diameter, larval length, larval weight, pupa length, and pupa weight. The research began with searching for S. frugiperda larvae in corn fields in Bantul Regency, Yogyakarta. Feeding treatments and observations of the S. frugiperda life cycle were conducted in the laboratory. Data analysis used was Kruskal-Wallis non-parametric test. The results showed that S. frugiperda on Zea mays leaves (control) had a life cycle length of 44 days, Pennisetum purpureum leaves 46 days, and Paspalum conjugatum leaves 49 days. Head diameter, length, and weight of S. frugiperda larvae at instar 3 and instar 4 were highest in corn leaf feed, but when entering instar 5 and instar 6 the highest values were found in the feed treatment with Paspalum conjugatum leaves. The coslusion of this research were Pennisetum purpureum leaves and Paspalum conjugatum leaves can be an alternative feed for breeding S. frugiperda in the laboratory.